(3OjhGf GHf GdeYde GdhGSWjs - (3CHhGdZfGFe fLe GdOjf eMeO Hf Ydj Hf aGQS GdgQKj GdhGSWj, GHf GdeYde,J (B592 (3g` s ((3CMeO Hf MSjf Hf CMeO Hf Ydj Hf YHOGdLHGQ s)
(3ChdgG (B:s
(3eHJhQ hHg JeRjb hChd GdehLhO efg(B: (3hejdG Edi LHdj RQhO aajgG s
(3BNQgG (B:s
(3hgd ojLjH dSGf Ch jQi HUQ hGdOeY WGQbI hGdfOH TGZdg s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B167s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B215 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B768s
Keywords: (3GdCOHs